Low-grade Appendiceal Mucinous Neoplasm (Appendiceal Villous Adenoma) with Cystic Fibrosis: A Case Report - Doğan, Emrah; Hakan Avcı, Hakan; Avcı, Muge Kuzu; Bozkurt, Korkut; Tapan, Ozge Oral; Tapan, Utku (Lietuvos chirurgija, 2021)
Cystic fibrosis (CF) is an autosomal dominant disease characterized by the dysfunction of exocrine secretory glands resulting from a mutation in the transmembrane regulator protein (CFTR) gene. As life expectancy increases in patients with cystic fibrosis secondary to advances in treatment, advanced age malignancies secondary to cystic fibrosis emerge. Especially, the frequency of gastrointestinal system malignancies and colon cancers increases with aging. Appendiceal tumors are a rare entity and constitute less than 1% of gastrointestinal tumors. We presented a villous adenoma encountered in an 18-year-old male patient with CF accompanied by clinical and radiological findings. Our case is the first reported appendiceal tumor that emerged in patients with cystic fibrosis.